Online Mentoring as an Extracurricular Measure to Encourage Talented Girls in STEM (Science, Technology, Engineering, and Mathematics): An Empirical Study of One-on-One Versus Group Mentoring. (July 2017) - Stoeger, Heidrun; Hopp, Manuel; Ziegler, Albert
Online mentoring provides an effective means of extracurricular gifted education for talented girls in science, technology, engineering, and mathematics (STEM). Comparative studies on the effectiveness of one-on-one versus group mentoring are lacking, however. The authors investigated this question in the context of a Germany-wide online mentoring program that employed both approaches. Study participants were girls enrolled in high-achiever-track secondary education in Germany ( N = 347) who were mentored online by female academics in STEM for 6 months, in either one-on-one ( N = 156) or group mentoring ( N = 191). It was assumed that the specific many-to-many group-mentoring condition examined in our study would be more effective than the one-on-one mentoring condition with respect to (a) the proportion of STEM communication and (b) the extent of STEM-related networking, both of which are important predictors of successful mentoring. Furthermore, the authors (c) expected more growth in elective intentions for the group-mentoring participants and (d) assumed that participants' centrality in their respective STEM networks would predict this increase. The study presents empirical support for all four assumptions and thus suggests that the special form of group mentoring examined here may be a more successful measure of extracurricular gifted education for girls in STEM than one-on-one mentoring.